Система сбора и подсчёта голосов в среде интернет-голосования - Жугель, Е. Ю. (ХНУРЕ, 2019)
Nowadays, the creation of clear, accurate, autonomous and secure voting system is very urgent problem. It’s very important in any election to find the most impartial and secure way to collect and count votes. In this work I’ve described a modern solution and presented my own way how to deal with that problem.